Pelatihan Prosedur Penginputan Nilai Siswa Pada Aplikasi E-Rapor SMA Negeri 1 Lobbo Talaud: Pelatihan Prosedur Penginputan Nilai Siswa Pada Aplikasi E-Rapor SMA Negeri 1 Lobbo Talaud - Sampetoding, Eliyah Acantha M; Balango, Iden; Potoboda, Relly (Bakti Sekawan : Jurnal Pengabdian Masyarakat, 2021)
The procedure for inputting student grades in the e-report application at SMA Negeri 1 Lobbo is generally very important considering the purpose of inputting grades is a method that must be done carefully and competently among teachers, both subject teachers, and homeroom teachers. So that there are no errors or mistakes in inputting data and values ??in the E-Report application. In Student Service, several literature reviews are explained, namely procedures, input, data, grades, schools, students, applications, E-Reports, and SMA. The purpose of this service is to find out how the Procedure for Inputting Student Values ??in the E-Report Application at SMA N 1 Lobbo and what problems are often faced. So that the author can consider and can provide input, encouragement, for the procedure for Inputting Student Values ??in the E-Report Application at SMA Negeri 1 Lobbo. In writing this Field Work Practice report, the authors conducted observations, interviews, to obtain result data consisting of profiles, history, vision and mission of SMA Negeri 1 Lobbo, organizational structure, tasks and functions as well as several ways to input student scores on the E-mail application. Reports from before.